Subsequent use of documents disclosed in civil proceedings - Gibbons, S; Susan M C Gibbons (2002)
Rule 31.22 of the Civil Procedure Rules 1998 provides, as a general rule, that those who receive documents through disclosure during civil proceedings may use them only for the purpose of the proceedings at hand. The general rule is subject to three exceptions, and judges have discretion to authorise subsequent use for other purposes. However, the foundational presupposition underpinning CPR 31.22 is that subsequent use, generally speaking, is improper. The thesis has two primary aims: (1) to demonstrate that the rule governing subsequent use (as developed in the case law) is theoretically and practically flawed, and that maintaining a blanket, general rule against subsequent use is unsound in principle, unjust, and procedurally inefficient; and (2) to generate a normative and procedural framework suitable for reform. Part I outlines the content, origins and operation of CPR 31.22. Through historical analysis, it suggests that presumptively categorising as improper all forms of subsequent use beyond the original litigation contradicts traditional authority. By identifying and examining the three principal rationales said to justify the modern rule, it argues that none affords sound justification. By analysing the exceptions to the rule, including judicial discretion, it seeks to show that such measures are incapable of remedying the defects in the underlying rule. Part II attempts to formulate a theoretically defensible, procedurally viable model for reforming CPR 31.22. It suggests that the presumption against subsequent use should be abolished, and the law reoriented around two central norms: the harm principle and a balancing approach. It tests this theoretical model by applying it to seven paradigmatic categories of subsequent use. Finally, it outlines a possible structure for procedural reform.